TEKNIK DAN INSTRUMEN ASESMEN RANAH PSIKOMOTORIK TEKNIK NON TES DAN PENERAPANNYA DALAM PENDIDIKAN ANAK USIA DINI - farihah, elyaum (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2022)
This article is motivated by the importance of assessment in the psychomotor domain. Assessment of psychomotor learning outcomes can be done with an action test or a performance test on the skills that have been mastered by students. The psychomotor domain is concerned with learning outcomes of skills and the ability to act. Assessment techniques in psychomotor assessment, namely, project assessment and portfolio assessment. There are six aspects of the psychomotor domain of non-test techniques, namely reflex movements, basic movement skills, perceptual abilities, harmony or accuracy, complex skill movements, and expressive and interpretive movements. Then, the instrument assessment tool in the psychomotor realm uses a rating scale, check list and anecdote notes.